Sustainability disclosure in SMEs – Evidence on the state of the art from the Euronext Growth Milan market - Bartolini, Monica; Moschini, Giorgia (Piccola Impresa / Small Business, 2025)
Purpose. This research explores how and to what extent Italian listed SMEs disclose sustainability information. As public companies, these SMEs are supposed to be dynamic and competitive, and, according to the legitimacy theory, they should also be incentivised to enhance disclosure transparency across all forms of capital and impact. This paper aims to deepen the understanding of their disclosure practices, an underexplored topic in the SMEs context. Assessing the quantity and quality of non-financial disclosure is crucial for identifying the challenges these firms face in meeting new EU and national regulations, voluntary standards and the increasing expectations of stakeholders. Methodology. This research focuses on annual reports and supplementary information available on websites to capture multiple aspects of sustainability reporting. It investigates the extent and forms of disclosure, offering a qualitative overview of reporting practices. A content analysis of sustainability information was conducted to evaluate the quality and comprehensiveness of the materiality assessment, considering the steps taken, methods and tools used, and the concept of materiality adopted. Findings. This study examines the current state of non-financial disclosure among listed SMEs, revealing that they are still far from fully complying with the theory, recent regulations, and standards established by international bodies. In doing so, this research highlights limitations and gaps of current practice regarding both the quantity and quality of sustainability disclosure. Practical and social implications. From a theoretical perspective, this study enhances understanding of SMEs' willingness to engage in more integrated and transparent disclosure to gain stakeholders’ legitimacy. From a practical standpoint, it highlights the existing gap between theory and practice, clarifying the challenges SMEs face in adapting to an evolving and increasingly demanding regulatory environment. Originality. This study contributes to the limited literature on sustainability disclosure in SMEs – a timely issue given the growing stakeholder and regulatory attention.